The antiepileptic drug levetiracetam promotes neuroblast differentiation and expression of superoxide dismutase in the mouse hippocampal dentate gyrus via PI3K/Akt signalling. (1st January 2018) - Yan, Bing Chun; Shen, Hui; Zhang, Yuanyuan; Zhu, Xiaolu; Wang, Jie; Xu, Pei; Jiang, Dan; Yu, Xing
Highlights: Levetiracetam enhanced cell proliferation and neuroblast differentiation. Levetiracetam promotes expression of antioxidants in the hippocampus. PI–3K/AKT signal pathway is involved to the antioxidants effect of Levetiracetam. Abstract: Levetiracetam (LEV), a second-generation antiepileptic drug, is commonly prescribed to treat certain types of seizures. Few studies have investigated the effects of LEV on hippocampal neurogenesis and its related mechanisms. In the present study, we investigated the effects of LEV on cell proliferation and neuronal differentiation in the mouse hippocampal dentate gyrus (DG). We here demonstrate a dose-dependent increase in Ki-67-immunoreactive cells in the subgranular zone of the DG in LEV-treated mice, and doublecortin-immunoreactive cells were also significantly increased in the hippocampal DG of mice treated with LEV. The above results indicate that LEV could improve cell proliferation and neuroblast differentiation in the hippocampus. In addition, we also found that LEV treatment improved superoxide dismutase (SOD)2, catalase and Gpx-1 levels and increased phosphatidylinositol 3-kinase (PI3K) and phosphorylated Akt protein levels in the hippocampus. Further investigation of the molecular mechanisms underlying these effects revealed that PC12 cell was blocked by a pharmacological inhibitor of PI3K (LY294002), and that LEV treatment rapidly activated PI3K/Akt and SOD2, catalase and Gpx-1. In brief, our results indicate that LEV enhanced cell proliferation and neuroblast differentiation by increasing the expression of antioxidants and PI3K and the level of phosphorylated Akt in the mouse hippocampus.